Seasonal wind pattern model development for coral reef monitoring - Deros S.N.M.; Din N.M.; Norzeli S.; Asmat A.; Mansor S. (Science and Engineering Research Support Society, 2023)
Wind pattern model development is vital for coral reef monitoring due to its dependency on sea surface wind. Wind in Malaysia is influenced primarily by four monsoon season; Northeast and Southwest monsoon with two transition period; April and October inter monsoon and categorized as low wind with annual mean speed of 3-5 m/s. Current wind study utilized limited wind data hence neglects the seasonal characteristics of wind behaviour in wind pattern model simulation. In this study, the Mixed-Layer Conveyor (MLC) model was adopted to simulate wind parameters such as wind speed distribution, direction, days in distinct monsoon to derive cumulative wind of distinct season. This can be used to describe wind behaviour of distinct monsoon season on coral reef growth. Result shows that the derived cumulative wind fit with an actual wind data (0.89). The model developed has an ability to derive seasonal wind cumulative productivity data to be used in estimation of the highest wind and lowest wind production. 2019 SERSC.